Semiotika Strukturalisme Saussure - Fanani, Fajriannoor (Jurnal The Messenger, 2013)
Ferdinand de Saussure is widely known as one of the prominent contributor to the theories of sign and language in semiotic. His theory in semiotic create a mark in the history of semiology. His semiotic was also known as one of the foundation of structuralism that growth in France. Structuralism, later become a movement that widespread not only in the field of linguistic but to the field of humanities and social sciences in general. How his semiotic works and how his view on structuralism applied in world of sign and language are interesting object. This writing try to overview all this in a simple and understandable way